2022
DOI: 10.1103/physrevb.105.125401
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring in bimetallic core-shell nanoparticles: Real-time observation

Abstract: The formation process of core-shell bimetallic nanoparticles synthesized by sputtering onto a substrate is observed in real time using an originally developed acoustic technique. The technique enables us to evaluate the structural change of nanoparticles at room temperature without contacting the nanoparticles or substrate. In the experiments, the sputtering of metal A followed by metal B tended to form B-shell/A-core nanoparticles. However, in Pd-Au alloy system, notable restructuring occurred during synthesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Early studies of the dynamics and thermodynamics of nanoalloys [5][6][7][8][9]11,[15][16][17][18][19][20][21] evolved into an area of intense ongoing research activity (see, e. g., Refs. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and the citations therein). Dynamical properties of 13-atom Ni/Al clusters have been explored and characterized using global descriptors such as caloric curve, RMS bond length fluctuation in the entire system, and specific heat.…”
Section: Results and Analysesmentioning
confidence: 99%
“…Early studies of the dynamics and thermodynamics of nanoalloys [5][6][7][8][9]11,[15][16][17][18][19][20][21] evolved into an area of intense ongoing research activity (see, e. g., Refs. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and the citations therein). Dynamical properties of 13-atom Ni/Al clusters have been explored and characterized using global descriptors such as caloric curve, RMS bond length fluctuation in the entire system, and specific heat.…”
Section: Results and Analysesmentioning
confidence: 99%
“…To better understand such trends, the alloying properties of platinum and palladium should be considered. A number of studies have focused on the structural characteristics of Pt–Pd particles, with a large number reporting that Pd tends to segregate to the surface of alloy particles. It was shown using diffusion coefficient and atomic distribution function that Pd migrates and segregates in the outer layers of Pt–Pd alloy nanoparticles. , Also, the phase separation and formation of Pd single crystals on the top of the Pt core were reported. , One should also mention that segregation of the palladium on the surface is not systematic, and there were some reports when Pd took the core , or more complex structures were formed. , The formation of an outer layer of palladium in the bimetallic Pt–Pd/TiO x catalyst can explain the difference in morphology compared with the monometallic Pt/TiO x catalyst in Figure . A layer of Pd oxide can effectively suppress the diffusion of Pt atoms and thus thermodynamically and kinetically stabilize the particles. ,, Indeed, the in situ NAP-XPS measurements presented in Figure confirmed that Pd enriches the surface during the restructuring of the bimetallic catalyst while undergoing the first temperature ramp.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have focused on the structural characteristics of Pt–Pd particles, with a large number reporting that Pd tends to segregate to the surface of alloy particles. 42 46 It was shown using diffusion coefficient and atomic distribution function that Pd migrates and segregates in the outer layers of Pt–Pd alloy nanoparticles. 47 , 48 Also, the phase separation and formation of Pd single crystals on the top of the Pt core were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The resistive spectroscopy has previously been used for fabricating nanoparticles with nanogaps 26,27 . However, in our previous work 17 , it was demonstrated that this method is applicable to investigate structural evolution of core-shell nanoparticles fabricated by sequential sputtering. In this study, it is applied to the co-sputtered nanoparticles to investigate what kind of growth process and internal structure occurs during the fabrication.…”
Section: Methodsmentioning
confidence: 99%
“…In-situ characterization is performed during dewetting using the dynamic transmission electron microscope 16 , but real-time structural characterization is hardly performed. Under these circumstances, we have developed a methodology, in which the formation process is monitored from the nanoparticle shape measured through the resonant vibration of a piezoelectric oscillator 17 . Using this method, in this study we investigate the formation process of Pd-based bimetallic nanoparticles synthesized by the co-sputtering.…”
Section: Introductionmentioning
confidence: 99%